2020
DOI: 10.1039/c9fo01740b
|View full text |Cite
|
Sign up to set email alerts
|

Chronic oral exposure to glycated whey proteins increases survival of aged male NOD mice with autoimmune prostatitis by regulating the gut microbiome and anti-inflammatory responses

Abstract: Glycated whey proteins modulate the gut microbiome and are anti-inflammatory in aged male NOD mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…Besides the main results from nal conditional Logistic regression analyses, we also found signs of gut microbial dysbiosis indicated by signi cantly differentiated relative abundances in other taxa. For instance, SCFA producing Anaerostipes was under-represented in GDM group and has been previously found nominally associated with type 2 diabetes mellitus [26], which was elevated along with alleviation of in ammation in animal models [27,28]. On the other hand, we found several taxa including Ruminococcaceae spp., Veillonellaceae and opportunistic pathogens Enterobacteriaceae of Proteobacteria were signi cantly over-represented in GDM cases.…”
Section: Discussionsupporting
confidence: 57%
“…Besides the main results from nal conditional Logistic regression analyses, we also found signs of gut microbial dysbiosis indicated by signi cantly differentiated relative abundances in other taxa. For instance, SCFA producing Anaerostipes was under-represented in GDM group and has been previously found nominally associated with type 2 diabetes mellitus [26], which was elevated along with alleviation of in ammation in animal models [27,28]. On the other hand, we found several taxa including Ruminococcaceae spp., Veillonellaceae and opportunistic pathogens Enterobacteriaceae of Proteobacteria were signi cantly over-represented in GDM cases.…”
Section: Discussionsupporting
confidence: 57%
“…Cronin et al found that WP supplementation experienced a significant alteration in the β-diversity of the intestinal flora [ 14 ]. Chen et al reported that WP-derived early EGPs could increase the survival rate of aged male NOD mice, and decrease metabolic syndrome in immune infiltration [ 15 ]. These pieces of evidence indicated that WP could maintain body health and repair damage in many ways.…”
Section: Introductionmentioning
confidence: 99%
“…Lactobacillus species exerts protective effects on intestinal integrity and immune responses of the animal infected with Clostridium [25]. The improvement of anti-inflammatory status has been reported to be followed by the increase in the abundance of Prevotella [26]. Intestinal barrier injury is closely associated with numerous factors, such as bacterial infection, inflammation, and mechanical damage; all of which can be caused by Helicobacter and Escherichia_Shigella infection [27,28].…”
mentioning
confidence: 99%